A Comparative Effectiveness Trial of Depression Collaborative Care: Subanalysis of Comorbid Anxiety. (July 2019) - Choi, Kristen R.; Sherbourne, Cathy; Tang, Lingqi; Castillo, Enrico; Dixon, Elizabeth; Jones, Andrea; Chung, Bowen; Eisen, Carol; Wells, Kenneth
The purpose of this exploratory subanalysis was to compare the effects of two depression quality improvement approaches on clinical outcomes and service utilization for individuals with comorbid depression/anxiety. This study used data from Community Partners in Care (CPIC), a cluster-randomized comparative effectiveness trial ( N = 1, 018; depression = 360; comorbid depression/anxiety = 658). Each intervention arm received the same quality improvement materials, plus either technical support (Resources for Services, RS) or support for collaborative implementation planning (Community Engagement and Planning, CEP). For the comorbid depression/anxiety subgroup, the collaborative planning arm was superior at improving mental health-related quality of life and mental wellness, as well as decreasing behavioral hospitalizations and homelessness risk at 6 months. The effects were not significant at 12 months. A collaborative planning process versus technical support for depression quality improvement can have short-term effects on mental wellness and social determinants of health among those with comorbid depression/anxiety.